Share

# Prove the Following Trigonometric Identities (1 + Tan^2 Theta)/(1 + Cot^2 Theta) = ((1 - Tan Theta)/(1 - Cot Theta))^2 = Tan^2 Theta - CBSE Class 10 - Mathematics

#### Question

Prove the following trigonometric identities

(1 + tan^2 theta)/(1 + cot^2 theta) = ((1 - tan theta)/(1 - cot theta))^2 = tan^2 theta

#### Solution

We have to prove (1 + tan^2 theta)/(1 + cot^2 theta) = ((1 - tan theta)/(1 - cot theta))^2 = tan^2 theta

Consider the expression

(1 + tan^2 theta)/(1 + cot^2 theta) = (1 + tan^2 theta)/(1 + 1/(tan^2 theta))

= (1 +tan^2 theta)/((tan^2 theta + 1)/tan^2 theta)

= tan^2 theta (1 + tan^2 theta)/(1 + tan^2 theta)

= tan^2 theta

Again, we have

((1 - tan theta)/(1 - cot theta))^2 = ((1 - tan theta)/(1 - 1/(tan theta)))^2

= ((1 - tan theta)/((tan theta - 1)/tan theta))

= tan^2 theta ((1 - tan theta)/(tan theta - 1))^2

= tan^2 theta ((1 - tan theta)/(1 -  tan theta))^2

= tan^2 theta(-1)^2

= tan^2 theta

Is there an error in this question or solution?

#### Video TutorialsVIEW ALL [6]

Solution Prove the Following Trigonometric Identities (1 + Tan^2 Theta)/(1 + Cot^2 Theta) = ((1 - Tan Theta)/(1 - Cot Theta))^2 = Tan^2 Theta Concept: Trigonometric Identities.
S